2002
DOI: 10.1002/j.1556-6678.2002.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Adventure Based Counseling: An Innovation in Counseling

Abstract: Increasingly, Adventure Based Counseling (ABC) is recognized as providing a significant means to help clients. This article describes the outdoor and indoor adventure experience and its relationship to counseling. A conceptual framework of ABC has been developed to provide a better understanding of the process and potential benefits of this approach and to serve as a model for researchers. Counseling theories, educational theories, setting, programming, processing, and transferring client gains to real life ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 34 publications
0
74
0
16
Order By: Relevance
“…Adventure therapy is closely related to, or synonymous, with a variety of other terms, including wilderness therapy [3,4], wilderness adventure therapy [5], wilderness experience programs [6], bush adventure therapy [7], adventurebased counselling [8][9][10], outdoor adventure intervention [1], therapeutic camping [11], and outdoor behavioral healthcare [12]. Gass et al [2] suggested that adventure therapy involves prescriptive use of adventure experiences by mental health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Adventure therapy is closely related to, or synonymous, with a variety of other terms, including wilderness therapy [3,4], wilderness adventure therapy [5], wilderness experience programs [6], bush adventure therapy [7], adventurebased counselling [8][9][10], outdoor adventure intervention [1], therapeutic camping [11], and outdoor behavioral healthcare [12]. Gass et al [2] suggested that adventure therapy involves prescriptive use of adventure experiences by mental health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Etapas del proceso de la cultura informacional (ALA, 2000, p.20) La (UNESCO, 2008) menciona que para vivir, aprender y trabajar en una sociedad rica en información, y basada en el conocimiento, los estudiantes y docentes deben utilizar con eficacia, la tecnología digital, por lo que, en un contexto educativo eficiente se debe ayudar a los estudiantes a adquirir capacidades para llegar a ser competentes, proceso que se desarrolla en forma progresiva como se presenta en la Figura 1. Las innovaciones pedagógicas son muy importantes, dado que en los últimos años el desarrollo del conocimiento, la ciencia y la tecnología se incrementan considerablemente, de tal modo que las teorías y programas educativos se implementan considerando la realidad en que los programas están desfasados respecto a la realidad, conciencia de la realidad, deseo de adquirir conocimiento y capacidad de cambios (Fletcher & Hinkle, 2002;Margalef García & Pareja Roblin, 2008).…”
Section: Gestión De La Informaciónunclassified
“…Both wilderness and adventure theory have developed out of experiential learning theories (Fletcher & Hinkle, 2002). The experiential learning process is the foundation of WT, which emphasizes the acquisition of life skills through challenge activities and the transfer of those skills into real life situations (Nadler & Luckner, 1995).…”
Section: Foundations Of Wtmentioning
confidence: 99%
“…WT immerses youth in an unfamiliar environment in which they often live with peers, participate in individual and group psychotherapy under licensed professionals, and learn skills that parallel real life struggles with the hope that they will incorporate these new skills into their repertoire when they return to their families (Russell, 2003). Since most therapeutic endeavors work to improve comfort for the client, this aspect makes WT especially distinct in that it utilizes perceived risk in the therapeutic paradigm (Fletcher & Hinkle, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation